2004
DOI: 10.1111/j.1440-0979.2004.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health services responding to men and their anger

Abstract: Due to their propensity for acting out with antisocial behaviours, angry men are often regarded as having antisocial personality disorder with little hope for treatment success. Whilst not denying the difficulties in working with angry men, this paper looks to challenge some of the received wisdom in this area. Antisocial personality disorder is compared with borderline personality disorder and the many similarities, including the association with childhood trauma, course of illness, symptoms and rates of occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…It is possible that stoicism increases as part of age-related maturity, due to increased acceptance of loss as inevitable (Judd et al, 2006). Likewise, there are authors who have explained it as a cohort effect; that is, that older individuals have grown up in a culture that values abnegation and resignation (Corboy, McLaren, Jenkins, & McDonald, 2014;Stewart & Harmon, 2004;Wrigley, Jackson, Judd, & Komiti, 2005), as well as stoical attitudes, for instance as regards pain, and the propensity to hide it and not seek help to avoid appearing weak (Judd et al, 2006;Yong, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that stoicism increases as part of age-related maturity, due to increased acceptance of loss as inevitable (Judd et al, 2006). Likewise, there are authors who have explained it as a cohort effect; that is, that older individuals have grown up in a culture that values abnegation and resignation (Corboy, McLaren, Jenkins, & McDonald, 2014;Stewart & Harmon, 2004;Wrigley, Jackson, Judd, & Komiti, 2005), as well as stoical attitudes, for instance as regards pain, and the propensity to hide it and not seek help to avoid appearing weak (Judd et al, 2006;Yong, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of positive attitudes toward those with mental health problems and optimizing health outcomes has been widely discussed in the literature (Holmqvist & Armelius, 2004; Horsfall, 1999; Read & Harre, 2001; World Psychiatric Association, 2001). In Australia, concern about negative attitudes toward those with mental health problems has increasingly been the focus of mental health commentary (Department of Human Services, 2002; Hugo, 2001; Jorm, Korten, Jacomb, Christensen, & Henderson, 1999; Stewart & Harmon, 2004). The Equal Opportunities and Human Rights Commission (2005) concluded that insufficient attention has been directed toward responding constructively to consumers and carers' experiences of mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, men report struggling to reclaim the strength and independence that is threatened by the lived experience of depression, but is demanded of them by dominant gender norms and practices (Emslie et al, 2006; O’Brien et al, 2005). Research also suggests that depression can be perceived as a risk to one’s “status” relative to other men and women (Courtenay, 2000) and that men show strength through restricted emotionality and denial of vulnerability (Gough, 2013; Stewart & Harmon, 2004).…”
mentioning
confidence: 99%